Hubungan Antara Tingkat Pengetahuan Ibu dengan Sikap dan Perilaku Ibu Terhadap Pemberian Imunisasi Dasar pada Bayi di Desa Penatih Dangin Puri - Eka Pratiwi, Ni Putu Lisa; Seri Ani, Luh (E-Jurnal Medika Udayana; Vol 6 No 10 (2017): E-Jurnal Medika Udayana, 2017)
Twenty seven million children under five years and 40 million pregnant women worldwide have not received routine immunization services. The infant mortality rate (IMR) in Indonesia is about 35 per 1000 live births and the under five mortality rate is 46 per 1000 children every year. Approximately 1.7 million children death in Indonesia or 5% of death by the age of five in Indonesia was caused by diseases preventable by immunization. This study is a quantitative research with cross sectional approach. 79 mothers with chidren aged 1-4 years old was chosen using purposive sampling from Penatih Dangin Puri village. The research was conducted during October to November 2014. Most of the samples show good knowledge (50,6%), good attitude (65,8%) and good behavior (65,8%) regarding immunization. There is a significant relationship (Spearman’s rank correlation, ? = 0,00) between knowledge and attitude regarding immunization. There is a significant relationship between knowledge (Spearman’s rank correlation, ? = 0,00) and attitude (Spearman’s rank correlation, ? = 0,00) with behavior regarding immunization.